Kinetics of the reaction of CO3˙−(H2O)n, n = 0, 1, 2, with nitric acid, a key reaction in tropospheric negative ion chemistry. Issue 16 (23rd February 2018) - van der Linde, Christian; Tang, Wai Kit; Siu, Chi-Kit; Beyer, Martin K.
Abstract : One water molecule accelerates the reaction of CO3 ˙ − with HNO3, while two water molecules quench the reactivity. Abstract : A significant fraction of nitrate in the troposphere is formed in the reactions of HNO3 with the carbonate radical anion CO3 ˙ − and the mono- and dihydrated species CO3 ˙ − (H2 O)1, 2 . A reaction mechanism was proposed in earlier flow reactor studies, which is investigated here in more detail by quantum chemical calculations and experimental reactivity studies of mass selected ions under ultra-high vacuum conditions. Bare CO3 ˙ − forms NO3 − (OH˙) as well as NO3 −, with a total rate coefficient of 1.0 × 10 −10 cm 3 s −1 . CO3 ˙ − (H2 O) in addition affords stabilization of the NO3 − (HCO3 ˙) collision complex, and thermalized CO3 ˙ − (H2 O) reacts with a total rate coefficient of 6.3 × 10 −10 cm 3 s −1 . A second solvent molecule quenches the reaction, and only black-body radiation induced dissociation is observed for CO3 ˙ − (H2 O)2, with an upper limit of 6.0 × 10 −11 cm 3 s −1 for any potential bimolecular reaction channel. The rate coefficients obtained under ultra-high vacuum conditions are smaller than in the earlier flow reactor studies, due to the absence of stabilizing collisions, which also has a strong effect on the product branching ratio. Quantum chemical calculations corroborate the mechanism proposed by Möhler and Arnold. The reaction proceeds through a proton-transferred NO3 − (HCO3 ˙) collision complex, which can rearrange to NO3 − (OH˙)(CO2 ). The weakly bound CO2 easily evaporates, followed by evaporation of the more strongly attached OH˙, if sufficient energy is available.